A facile preparation method for nanosized MOFs as a multifunctional material for cellular imaging and drug delivery. Issue 6 (3rd June 2017) - Park, Kyeng Min; Kim, Hyunuk; Murray, James; Koo, Jaehyoung; Kim, Kimoon
Abstract: Tb-based metal-organic framework nanoparticles (Tb-MOF NPs) with good colloidal stability and stable fluorescence properties in an aqueous solution were prepared by a simple mechanical grinding of Tb-MOF with a biocompatible polymer surfactant (F127). The characteristic fluorescence property of Tb-MOF NPs allowed us to use this nanomaterial as a cell imaging probe. Efficient cellular uptake of Tb-MOF NPs apparently via an energy-dependent endocytosis was observed by confocal laser scanning microscopy. By taking advantage of the porous nature of the Tb-MOF NPs an anticancer drug (doxorubicin) was successfully loaded and delivered to kill cancer cells to demonstrate their usage as a drug delivery vehicle. This simple grinding method afforded a nanosized, multifunctional biomaterial that was used for cell imaging and drug delivery, and it can be extended to other MOFs to widen their applications. Abstract :